Microclimate diversity across sweet corn varieties and implications for agrobiodiversity in precision intercropping - CARLA FRIEDA PANTOUW; BRAYEN PATANDEAN; ARYA WIDURA RITONGA; MUHAMAD ACHMAD CHOZIN; AGUS RACHMAT (Society for Indonesian Biodiversity, 2025)
Abstract. Pantouw CF, Patandean B, Ritonga AW, Chozin MA, Rachmat A. 2025. Microclimate diversity across sweet corn varieties and implications for agrobiodiversity in precision intercropping. Biodiversitas 26: 5238-5247. The intercropping of sweet corn (Zea mays) and bird’s eye chili (Capsicum frutescens) is a promising land-use intensification strategy to improve resource-use efficiency while strengthening agrobiodiversity. This study evaluated four sweet corn varieties (Arinta, Exotic, Talenta, and Paragon) combined with two chili genotypes, Bonita (shade-loving) and Ori 212 (shade-tolerant), arranged in a Randomized Complete Block Design (RCBD) with four replications at the Pasir Kuda Experimental Station, Institut Pertanian Bogor, Bogor, Indonesia. Microclimate parameters (temperature, relative humidity, light intensity) were recorded with data loggers and lux meters, while chili morphophysiological traits included plant height, stem diameter, leaf area, and physiological responses. Results indicated that variation in sweet corn canopy architecture significantly altered microclimatic conditions. Exotic and Talenta reduced light intensity by 43% (to 35,000 lux), which favored the growth of Ori 212 (height 65.25 cm; leaf area 19.61 cm²). Paragon created the coolest and most humid microclimate (29.7°C; 61.95% RH), stimulating maximum leaf expansion in Bonita (20.98 cm²). Arinta maintained higher light levels (47,633 lux), while the open control (>62,000 lux) suppressed chili growth (height 25 cm; leaf area 6-9 cm²) due to heat stress and photoinhibition. Pearson correlation further revealed strong positive associations among photosynthesis, stomatal conductance, and transpiration, demonstrating that microclimate directly regulates chili physiological dynamics. In conclusion, sweet corn canopy diversity plays a decisive role in shaping niche differentiation for chili in intercropping systems. The Exotic-Ori 212 and Paragon-Bonita combinations emerged as the most compatible patterns for achieving balanced growth, photosynthetic efficiency, and strengthened agrobiodiversity in sustainable tropical farming systems.